Coverets kapital: En empirisk undersøgelse af genremærkatens betydning for vurderingen af det litterære værk - Nyboe, Jacob Ølgaard (K&K - Kultur og Klasse, 2017)
Based on a large survey (n=539) this study examines how book covers in general and the genre label in particular play a role in the aesthetic positioning and marketing of books. A given work can succeed with large sales numbers and economic capital as well as by obtaining more field specific cultural and social capital. These different ways of positioning oneself on the market are, according to Bourdieu, to a large extent inverse – and it is therefore hypothesized that they require different strategies. In order to examine this phenomenon, the respondents are split into two groups and asked to evaluate four different covers with respect to broad audience appeal. Furthermore, they are asked to give a short description of the content they would expect in the different books. The cover samples are identical for the two groups, but alternating genre labels have been removed in one of the groups while being preserved in the other. Based on the responses, it is confirmed that genre labels have a significant effect on the reception of and expectations to the work. It is also demonstrated how the commercial and artistic appeal varies among the four books indicating an effect of the paratext as a whole. It is indicated by its cover, to what extent a book targets commercial interests or strives for a more field specific capital and recognition – and the genre label is a salient part of this positioning.